Urban risk reduction an Asian perspective - Shaw, Rajib; Srinivas, Hari; Sharma, Anshu (Emerald Group Publishing Limited, 2009)
As cities all over the world have urbanized rapidly after the industrial revolution, most cities have confronted environmental problems such as poor air and water quality, high levels of traffic congestion and ambient noise, poor-quality build environment, derelict land, greenhouse gas emissions, urban sprawl, generation of waste and waste-water. In particular, cities in the developing world face problems related to the living conditions in which the urban population lives. In the context of urban cities in the developing world, it can be narrowed to the quality of life of living population in the cities. Needless to say that Asia has the largest population, as well as urban population at risk. This book brings the lessons from innovative urban risk management approaches in Asian cities, drawing the lessons from seven Asian countries. The authors of the chapters consist of wider spectrum of stakeholders: from academicians to policy makers to NGO practitioners.
Keywords: Risk management -- Asia.; Emergency management -- Asia.; Urban health -- Asia.; Urban ecology (Sociology) -- Asia.; elektronické knihy; electronic books